Female Consumers’ Involvement in Intentional Non-Sustainable and Unintentional Sustainable Apparel Decisions: An Emerging Market Perspective - Elizabeth Kempen; Rejoice Tobias-Mamina; Mariette Strydom; Lorna Christi; Mirriam Makopo (Journal of Marketing and Consumer Behaviour in Emerging Markets)
This study is aimed at determining consumers’ sustainable apparel involvement in the purchasing or disposing of apparel in an emerging market context (EMC). Consumers in developed countries show increased interest in sustainable apparel behaviour, contrary to emerging markets such as South Africa, which is indicative of the lowest level of sustainable apparel consumption. An exploratory descriptive qualitative research design was used to determine consumers’ involvement and was facilitated through eleven digitally recorded small focus groups with female apparel shoppers who make use of a custom-made apparel designers. The findings reveal intentional non-sustainable apparel decisions manifest through eco-uninvolved instore purchases and once-off commissioned designer apparel orders. Unintentional sustainable apparel behaviour is characterised by (1) in-store apparel purchases: signifying quality clothing, observed in the material and stitching, resulting in clothing items worn for longer and handed down from generation to generation, sensitivity to the origin of the garment and (2) apparel disposal behaviour such as (a) keeping apparel as cleaning material and repurposing into wearable apparel; (b) permanent disposal through handing down items and (c) temporary disposal through exchanged items. Applying the Elaboration Likelihood Model, it was possible to explain the lack of elaborated involvement in sustainable apparel practices resembling the peripheral route of the model. Unintentional sustainable practices have not been identified in the South African context, indicating the valuable contribution consumers in an emerging market context (EMC) can make if better awareness is created by the government and the retail sector specifically to address intentional non-sustainable purchasing behaviours in future.